Somos Hermanos : literatura de cárcere como testemunho, o caso de Diário de um detento: o livro, de Jocenir - Carvalho, Paulo Roberto Alves de (2011)
This paper aims to discuss the recognition of Prison Literature as a part of the Testimonial Literature genre. To explore the issue, this work takes a brief look into the connection between memorial and prison, taking the notions of Nancy Fraser, Axel Honneth and CharlesTaylor into account; as well as literary critics and historians, who recognize the testimonial narrative as an essential historiographical record. The text under investigation is the story of Diário de um detento: o livro (2001) by the ex-convict Jocenir, a crucial reference to Prison Literature in Brazil, which has been analyzed and collated with two other fundamental narratives: O que é isso, companheiro, by Fernando Gabeira and É isto um homem?, by Primo Levi, pointing out similarities and differences between the three records.